The relationship between plant species richness and soil pH vanishes with increasing aridity across Eurasian dry grasslands. Issue 4 (21st November 2016) - Palpurina, Salza; Wagner, Viktoria; von Wehrden, Henrik; Hájek, Michal; Horsák, Michal; Brinkert, Annika; Hölzel, Norbert; Wesche, Karsten; Kamp, Johannes; Hájková, Petra; Danihelka, Jiří; Lustyk, Pavel; et al.
Abstract: Aim: Soil pH is considered an important driver of fine‐scale plant species richness in terrestrial ecosystems. However, it is unclear to what extent this relationship is influenced by precipitation, which often directly affects both soil pH and species richness. We asked: (1) what is the relationship between fine‐scale vascular plant species richness and soil pH in regions with different levels of precipitation and (2) what are the relative effects of soil pH and precipitation on species richness? Location: Dry grasslands in eight regions of northern Eurasia. Methods: Species richness and soil pH were measured in 1055 10 m × 10 m plots and precipitation values were derived from global datasets. Relationships between variables were explored using general linear models, mixed‐effect models and partial regressions. Variation partitioning was used to assess the relative effect of each predictor on species richness. Results: In wetter regions, soil pH range was broader, mean species richness was higher and the richness–pH relationship was unimodal. In drier regions, mean soil pH was higher and its range narrower, species richness was on average lower and less variable, and the richness–pH relationship was negative or absent. The richness–pH relationship persisted after controlling for the effect of precipitation, but precipitation, uniquely or together with soil pH, explained more variation in species richness in most regions than did pH alone. Main conclusions: The relationship between plant species richness and soil pH in dry grasslands changes from unimodal, through negative, to none with decreasing regional precipitation in Eurasia. However, it seems that the species richness–soil pH relationship in dry grasslands over broad areas is substantially influenced and confounded by precipitation either indirectly, by shortening and shifting the pH gradient, or directly, by decreasing the negative effects of drought stress on richness.